Constructing the perception of ‘annoying’ words and phrases in interaction: An analysis of delegitimisation strategies used in interviews and online discussions in Finnish - Priiki Katri (Poland, 2025)
This study examines the linguistic metadiscourse on expressions perceived as ‘annoying’ and the strategies used to justify this perception. Two different types of data are examined in which verbal hygiene is practised in interaction: language biography interviews and anonymous online discussions. In the examined datasets, the discussion begins with an explicit question regarding annoying words and phrases. The themes discussed and the delegitimisation strategies adopted by a participant are affected by other participants. In interviews, minor reformulations of the question can be leading, and in online discussions, other writers regulate the debate with counter-arguments, which leads to a wider variety of delegitimisation strategies. The analysis also shows a counter-discourse to verbal hygiene.